Epoxide activation by a silver phosphonate for heterogeneous catalysis of CO2 cycloaddition. Issue 1 (2nd December 2022) - Gao, Chao-Ying; Mao, Chen; Yang, Yang; Xu, Ning; Liu, Jinglin; Chen, Xiaohong; Liu, Jinghai; Duan, Limei
Abstract : With Brønsted and Lewis acidic sites, a new Ag(i ) phosphonate has been developed and verified to have excellent performance in the cycloaddition reaction of CO2 and epoxides. Abstract : Hydrothermal reaction of silver nitrate and a tetraphosphonic acid (H8 L) affords a novel coordination polymer, with the general formula, [Ag10 (H3 L)2 (H2 O)2 (4, 4′-bipy)], denoted as compound 1 . It is built from extended ⋯Ag–O–P–O⋯ chains and organic linkers to form a 3D network. In its structure, three of four phosphonyl groups of the organic ligand are protonated, endowing compound 1 with rich Brønsted acid sites. With Brønsted and Lewis acidic sites, the catalytic activity of 1 was investigated through cycloaddition reaction of CO2 and epoxides, and the results displayed an excellent performance. Besides, the heterogeneous nature of compound 1 was proved by five cycle experiments with no significant compromise on the activity, indicating the silver phosphonate as an excellent catalyst for CO2 chemical fixation.